Dataset of differentially expressed genes in mouse P12 testes in response to the loss of ATRX in Sertoli cells - Stefan Bagheri-Fam (Data in Brief, 2022)
This dataset represents genes that are dysregulated in the postnatal day 12 (P12) mouse testis when ATRX is specifically inactivated in Sertoli cells (ScAtrxKO mice). The differentially expressed genes included in the dataset may play important roles in the testicular phenotypes observed in the ScAtrxKO mice, which were first reported in our previous work [1]. In fetal ScAtrxKO mice, Sertoli cells undergo apoptosis due to cell cycle defects, resulting in smaller testes with reduced tubule volume [1]. Adult ScAtrxKO mice show a wide range of spermatogenesis defects probably due to a failure of the dysfunctional ATRX protein to interact with the androgen receptor (AR) [1]. ATRX, a chromatin remodeling protein, is widely expressed in the human testis including Sertoli cells [2,3]. In XY individuals, the loss of ATRX leads to ATR-X (alpha thalassemia, mental retardation, X-linked) syndrome associated with a wide range of genital abnormalities such as hypospadias, ambiguous genitalia, and small testes with reduced tubule volume [4–8]. Our dataset contributes towards understanding the mechanism underlying ATRX regulation of testis development and spermatogenesis.